Analisis Pelaksanaan Zona Integritas di Kepolisian Resor Ternate Guna Terwujudnya Wilayah Bebas dari Korupsi - Wresni Haryadi; Abdul Rahman Jannang; Rahmat Sabuhari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Analysis of the Implementation of the Integrity Zone at the Ternate Police for the Realization of a Corruption-Free Area". With the supervisory commission of Abdulrahman Jannang and Rahmat Sabuhari. This study aims to analyze the Implementation of the Integrity Zone at the Ternate Police Resort in terms of 6 (six) areas of change which include Change Management, Management Arrangement, HR Management Arrangement, Strengthening Supervision, Strengthening Performance Accountability, and Improved Service Quality . This study uses a qualitative descriptive method involving 8 informants as well as a study of study documentation. The results of the study show that the implementation of the Integrity Zone at the Ternate Police from the aspect of change management is visible there is a commitment from the leadership and all service implementing units in building an Integrity Zone, this is shown by the performance of service officers who prioritize community satisfaction. The management arrangement shows that it is quite good, but there are still E-Office indicators that need to be encouraged to use so that the control system is more optimal. Structuring the HR management system still needs to increase the competence of HR in charge of public services, not all of the personnel on duty have the qualifications to take part in function training in service units . Strengthening performance accountability, from the administrative side, it has been very good in supporting the implementation of activities, but there are still visible deficiencies in the readiness of supporting infrastructure that is still lacking, especially the Traffic function service , Strengthening supervision, the supervision system is carried out in stages by involving several related functions to encourage the creation of transparent and free public services. from practices that lead to abuse of authority. Improving the quality of public services, there are still shortcomings in infrastructure facilities that are not adequate in supporting services to the community, especially the Traffic function, the unsupported facility is indicated by the absence of intensive coordination of the service function with the planning function for the provision of the required service facilities